Magnetoelectric control of spin currents - Gomez, Javier Enrique (2016)
The ability to control the spin current injection has been explored on a hybrid magnetoelectric system consisting of a (011)-cut ferroelectric lead magnesium niobate-lead titanate (PMNT) single crystal, a ferromagnetic FePt alloy, and a metallic Pt. With this PMNT/FePt/Pt structure we have been able to control the magnetic field position or the microwave excitation frequency at which the spin pumping phenomenon between FePt and Pt occurs. We demonstrate that the magnetoelectric heterostructure operating in the L-T (longitudinal magnetized-transverse polarized) mode couples the PMNT crystal to the magnetostrictive FePt/Pt bilayer, displaying a strong magnetoelectric coefficient of ∼140 Oe cm kV-1. Our results show that this mechanism can be effectively exploited as a tunable spin current intensity emitter and open the possibility to create an oscillating or a bistable switch to effectively manipulate spin currents.